Dramatic construction of bullying scenes in animated films (Al-Academy, 2023)
Given the importance of the phenomenon of bullying and its spread in the productions of animated films and the resulting impact on them, and the dominance of a large number of satellite channels that simulate different age stages and for both sexes. It is bullying others and their imitation of characters inspired by animated films with aggressive behavior that appears in them by imposing his authority by force on those who are weaker than him and in various methods that fall within the concept of bullying, and the interest of most satellite channels in this type of production that simulates different age groups, this research comes as an attempt A scientific method through which the researcher seeks to know the issue of the dramatic construction of bullying scenes in animated films and the drama embodied in their scenes by analyzing scenes from different samples in order to reveal them. Based on the foregoing, the research deals with an important aspect of the creative process in animation-oriented production, through the elements of the cinematic language, by identifying its expressive and semantic data. of job performance.